First-in-human safety and immunogenicity investigations of three adjuvanted reduced dose inactivated poliovirus vaccines (IPV-Al SSI) compared to full dose IPV Vaccine SSI when given as a booster vaccination to adolescents with a history of IPV vaccination at 3, 5, 12 months and 5 years of age. Issue 4 (23rd January 2017) - Lindgren, Line M.; Tingskov, Pernille N.; Justesen, Annette H.; Nedergaard, Bettina S.; Olsen, Klaus J.; Andreasen, Lars V.; Kromann, Ingrid; Sørensen, Charlotte; Dietrich, Jes; Thierry-Carstensen, Birgit
Highlights: Three adjuvanted reduced dose IPV-Al SSI were safe and immunogenic in adolescents. The three IPV-Al SSI were highly immunogenic, but inferior to IPV Vaccine SSI as a booster. Reduced dose IPV-Al SSI is intended for markets in need of affordable IPV. Abstract: Background: There is a demand of affordable IPV in the World. Statens Serum Institut (SSI) has developed three reduced dose IPV formulations adsorbed to aluminium hydroxide; 1/3 IPV-Al, 1/5 IPV-Al and 1/10 IPV-Al SSI, and now report the results of the first investigations in humans. Methods: 240 Danish adolescents, aged 10–15 years, and childhood vaccinated with IPV were booster vaccinated with 1/3 IPV-Al, 1/5 IPV-Al, 1/10 IPV-Al or IPV Vaccine SSI. The booster effects (GMTRs) of the three IPV-Al SSI were compared to IPV Vaccine SSI, and evaluated for non-inferiority. Immunogenicity results: The pre-vaccination GMTs were similar across the groups; 926 (type 1), 969 (type 2) and 846 (type 3) in the total trial population. The GMTRs by poliovirus type and IPV formulation were: Type 1: 17.0 (1/3 IPV-Al), 13.0 (1/5 IPV-Al), 7.1 (1/10 IPV-Al) and 42.2 (IPV Vaccine SSI). Type 2: 12.5 (1/3 IPV-Al), 13.1 (1/5 IPV-Al), 7.6 (1/10 IPV-Al) and 47.8 (IPV Vaccine SSI). Type 3: 14.5 (1/3 IPV-Al), 16.2 (1/5 IPV-Al), 8.9 (1/10 IPV-Al) and 62.4 (IPV Vaccine SSI) Thus, the three IPV-Al formulations were highly immunogenic, but inferior to IPV Vaccine SSI, in this booster vaccination trial. Safety results: No SAE and no AE of severe intensity occurred. 59.2% of the subjects reported at least one AE. Injection site pain was the most frequent AE in all groups; from 24.6% to 43.3%. Injection site redness and swelling frequencies were < 5% in most and < 10% in all groups. The most frequent systemic AEs were fatigue (from 8.2% to 15.0%) and headache (from 15.0% to 28.3%). Most AEs were of mild intensity. In conclusion, the three IPV-Al SSI were safe in adolescents and the booster effects were satisfactory. ClinicalTrials.gov registration number:NCT02280447 .